(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
India is now a rapidly growing country in terms of retails business, on track to achieve a half-million million sales locations by 2030. All of these factors are beneficial to Indian textile businesses in the long term. However, the global recession appears to be deteriorating with each day, as long as countries such as those in South and Southeast Asia continue to expand as well as thrive, fabric business will continue to thrive. The research paper aimed to learn about the socio-economic features of customers who prefer branded apparel and the variables that impact their decision to purchase branded apparel. Primary data were obtained from 200 customers using a questionnaire throughout Delhi to satisfy the goals. According to the findings of the survey, today’s customers are brand aware. They like branded apparel to seem more trendy, and branded apparels also reflect an individual’s prestige. Consumers choose branded apparel because they are more durable, has better diversity, and is of a high standard. Although there has been an attempt to identify the quality of products, pricing characteristics, and promotional characteristics that are engaged in planning, as well as whether that there’s any substantial association between demographic factors and purchasing behavior.